One stone for two birds: Endophytic fungi promote maize seedlings growth and negatively impact the life history parameters of the fall armyworm, Spodoptera frugiperda - Kinyungu, Sharon W.; Agbessenou, Ayaovi; Subramanian, Sevgan; Khamis, Fathiya M.; Akutse, Komivi S. (Frontiers in Physiology, 2023)
The fall armyworm(FAW) Spodoptera frugiperda, is a voracious pest of cereals native to the Americas and which invaded Africa in 2016. Chemical control is the main management option, which however remains ineffective and unsustainable. Fungal endophytes are increasingly used as alternative for the management of insect pests of economic importance. This study assessed the potential of eight endophytic fungal isolates to colonize maize plant and their ability to promote seedlings growth through seed and foliar inoculations, as well as their suppressive effects onFAW. Fungal colonization rates of different plantparts by the endophytes varied as per the inoculation methods. Beauveria bassianaICIPE279 colonized more than 60%of all the seedling parts while B.bassianaG1LU3 only colonized stem (25%) and leaf (5%) tissues through foliar inoculation. Trichoderma atrovirideF2S21, T.asperellumM2RT4, T.harzianumF2R41, Trichoderma spp.F2L41, HypocrealixiiF3ST1 and Fusarium proliferatumF2S51 successfully colonized all the plant parts and therefore were selected and further evaluated through seed inoculation for their endophytic persistence, effect on plant growth, and pathogenicity to S. frugiperda immature and adult stages. Weekly assessment showed varied effect of the endophytes on maize plant growth parameters compared to the control. During the first week, percentage colonization of the plant partsranges between 90-100%, 65-100%, and 60-100%, in the roots, stems, and leaves, respectively for all the five tested isolates. However,the colonization pattern/rates significantlydecreased over time for H.lixiiF3ST1 in the stems and leaves, and for T.harzianumF2R41 in the leaves and for T.asperellumM2RT4 in the roots. In addition, T.harzianumF2R41 outperformed all the other isolates in boosting the plant height, whereas H.lixiiF3ST1 and T. This is a provisional file, not the final typeset article asperellumM2RT4 outperformedall the other isolates in increasing the wet and dry shootsweight. Furthermore, the number of egg masses laid on endophytically-colonized maize plants varied among thetreatments. TrichodermaasperellumM2RT4 and H.lixiiF3ST1 endophytically-colonized maize plants significantly reduced the number of eggmasses and the defoliation/feeding rates of the pest compared tothe control. Additionally, T.harzianumF2R41 had the highest negativeimpact on thepupation and adultemergence of S.frugiperda with a female-biased sexratio. Our findings indicate that T.asperellumM2RT4, T.harzianumF2R41, and H.lixiiF3ST1 hold a potential to be developed as endophytic-fungal-based biopesticides for sustainablemanagement of S.frugiperda and as plant growthpromoters.